ANALISIS REVALUASI ASET DALAM LAPORAN KEUANGAN PT PLN TAHUN 2021 - Aprilia, Fatma Yunita; Fitriah, Luluk Desva; Budiwitjaksono, Gideon Setyo (Pusat Riset dan Inovasi Nasional, 2022)
Revaluation of fixed assets is a methode to revaluate company’s fixed assets to reflect the market value. Revaluation of assets can be done for accounting purposes, tax purposes, or accounting and tax purposes. Revaluation of fixed assets for tax purposes is regulated in the Regulation of the Minister of Finance No. 191/PMK.010/2015. The purpose of this study is to analyze the taxes that must be paid in 2021 as a result of the asset revaluation practice carried out by PT PLN (Persero). This study used a descriptive method with a qualitative approach. The object of this research is PT Perusahaan Listrik Negara (Persero). Data used for this research are 2021 financial statements of PT Perusahaan Listrik Negara (Persero) from its official website. The result of this study indicate that the revaluation of fixed assets for tax purpose by PT PLN in 2021 can reduce the totals of assets and its net income, furthermore the revaluation of fixed assets does not affect the income tax for the year after revaluation due to the loss of revaluation of fixed assets by PT PLN in 2021.